Expanding Valve Repair in Rheumatic Heart Disease - Afifi, Ahmed; Shehata, Nairouz; Nagi, Mohamed; Sultan, Abdel Rahman; Yacoub, Magdi (Frontiers in Cardiovascular Medicine, 2022)
Rheumatic heart disease is a serious ailment with significant morbidity and mortality in endemic areas; yet, there is no agreement on indication, timing, and surgical modality for treating rheumatic valve affection. There is mounting evidence that rheumatic mitral valve repair is possible with good long-term results, less is the case with rheumatic aortic valve disease. We discuss the surgical approach for both valves emphasizing the role of multimodality imaging.